Motor skills of toddlers with autism spectrum disorders. (March 2013) - Lloyd, Meghann; MacDonald, Megan; Lord, Catherine
With increased interest in the early diagnosis and treatment of children with autism spectrum disorders (ASD), more attention has been called to the motor skills of very young children with ASD. This study describes the gross and fine motor skills of a cross-sectional group of 162 children with ASD between the ages of 12 and 36 months, as well as a subset of 58 children followed longitudinally. Gross motor and fine motor age equivalent scores were obtained for all children. A 'motor difference' variable was calculated for each child's gross and fine motor skills by taking the absolute difference of the children's age equivalent motor score and their respective chronological age. In Study 1 (the cross-sectional analysis), ANCOVA (co-varied for nonverbal problem solving) revealed significant group differences in the gross motor and fine motor age difference variables. Post-hoc analysis revealed that gross motor and fine motor differences became significantly greater with each 6-month period of chronological age. In Study 2, 58 children were measured twice, an average of 12 months apart. Results indicate that the gross motor and fine motor difference scores significantly increased between the first and second measurements. The importance of addressing motor development in early intervention treatments is discussed.